The effect of passion fruit hulls level (Passiflora edulis Sims f. edulis Deg) as Kacang goat feed component: I. Intake digestibility and nitrogen retention - Kiston Simanihuruk; Komang G Wiryawan; Simon P Ginting (Jurnal Ilmu Ternak dan Veteriner, 2006)
To study the effect of utilization of passion fruit hulls (Passiflora edulis Sims f. edulis Deg) as feed component on consumption, digestion and nitrogen retention in kacang goats, a trial was conducted using 20 young kacang goats (average initial body weight 23.73±2.16 kg). The experiment was arranged in completely randomized design consisting of 4 diets and 5 replications. Animal were randomly allocated into 4 diets (0, 15, 30, 45% of passion fruit hulls). Each diet contains 2550 Kcal/kg metabolism energy and 14% crude protein. The feeding level was set at 3.8% of body weight based on dry matter. The results of the experiment showed that average dry matter intake, nutrient digestibility, and nitrogen retention were not affected by level of passion fruit hulls (P>0.05), although nutrient digestibility and nitrogen retention tended to decrease with the increasing level of passion fruit hulls. It was concluded that passion fruit hulls can be used till 45% level in the diet. Key Words: Passion Fruit, Consumption, Digestibility, Nitrogen Retention, Kacang Goat